Keratin-alginate sponges support healing of partial-thickness burns - Moay, Zi Kuang (2021)
Deep partial-thickness burns damage most of the dermis and can cause severe pain, scarring, and mortality if left untreated. This study serves to evaluate the effectiveness of crosslinked keratin-alginate composite sponges as dermal substitutes for deep partial-thickness burns. Crosslinked keratin-alginate sponges were tested for the ability to support human dermal fibroblasts in vitro and to support the closure and healing of partial-thickness burn wounds in Sus scrofa pigs. Keratin-alginate composite sponges supported the enhanced proliferation of human dermal fibroblasts compared to alginate-only sponges and exhibited decreased contraction in vitro when compared to keratin only sponges. As dermal substitutes in vivo, the sponges supported the expression of keratin 14, alpha-smooth muscle actin, and collagen IV within wound sites, comparable to collagen sponges. Keratin-alginate composite sponges supported the regeneration of basement membranes in the wounds more than in collagen-treated wounds and non-grafted controls, suggesting the subsequent development of pathological scar tissues may be minimized. Results from this study indicate that crosslinked keratin-alginate sponges are suitable alternative dermal substitutes for clinical applications in wound healing and skin regeneration.